nav

       HOME    BINUS EVENT   HOW TO   KBP   THOUGHTS

About



Monday, October 20, 2014

Assignment #4

Source:
Concepts of Programming Languages, Robert W. Sebesta.
Chapter 4: Lexical and Syntax Analysis, page 199-201

By:
Name : Helena Natanael
NIM  : 1801380333



Review Question:

6. What is a state transition diagram?
A state transition diagram, or just state diagram, is a directed graph. The nodes of a state diagram are labeled with state names. The arcs are labeled with the input characters that cause the transitions among the states. An arc may also include actions the lexical analyzer must perform when the transition is taken.

7. Why are character classes used, rather than individual characters, for the letter and digit transitions of a state diagram for a lexical analyzer?
A lexical analyzer is interested only in determining that it is a name and is not concerned with which specific
name it happens to be. Therefore, we define a character class named LETTER for all 52 letters and use a single transition on the first letter of any name. 


8. What are the two distinct goals of syntax analysis?
There are two distinct goals of syntax analysis. 

First, the syntax analyzer must check the input program, whether it's syntactically correct or not, and if an error is found, the analyzer must create a diagnostic message. However, the syntax analyzer must create an error list because it's possible to find many errors during a single analysis of the input program. So when it finds an error, it saves the diagnostic message and go on checking. If it is not done well, error recovery may create more errors, or at least more error messages. 

Second, it has to produce a complete parse tree, or at least trace the structure of the complete parse tree, for syntactically correct input. The parse tree (or its trace) is used as the basis for translation.

9. Describe the differences between top-down and bottom-up parsers.
The difference is in the making of parsers. 

Top-down: the tree is built from the root downward to the leaves
Bottom-up: the tree is built from the leaves upward to the root.

10. Describe the parsing problem for a top-down parser.
I usually use the bottom-up parsers, and I rarely use top-down parser, because it takes more concern and focus to make it correctly, there's bigger chance of bad parsing or skipped leaves in top-down parser. It also would be confusing if it comes to bad grammar/ambiguous grammar.


Problem Set: 

6. Given the following grammar and the right sentential form, draw a parse
tree and show the phrases and simple phrases, as well as the handle.
S → AbB | bAc
A → Ab | aBB
B → Ac | cBb | c

a. aAcccbbc
S → AbB → aBBbB → aAcBbB → aAccBbbB → aAcccbbc




Phrases: aAcccbbcaAcccb, Ac, ccb, c, c.

Simple Phrases: Ac, c, c


Handle: Ac


b. AbcaBccb
S → AbB → AbcBb → AbcAcb → AbcaBBcb → AbcaBccb


Phrases: AbcaBccb, caBccb, aBcc, aBc, c

Simple Phrases: c


Handle: c


c. baBcBbbc
S →  bAc → baBBc → baBcBbc → baBcBbbc



Phrases: baBcBbbc, aBcBbb, aBcBb, cBb.

Simple Phrases: cBb


Handle: cBb

7. Show a complete parse, including the parse stack contents, input string,
and action for the string id * (id + id), using the grammar and parse
table in Section 4.5.3.

8. Show a complete parse, including the parse stack contents, input string,
and action for the string (id + id) * id, using the grammar and parse
table in Section 4.5.3.

9. Write an EBNF rule that describes the while statement of Java or C++.
Write the recursive-descent subprogram in Java or C++ for this rule.
<while_stmt> -> WHILE ‘(‘ (<arith_expr> | <logic_expr>) ‘)’ <block> <block> -> <stmt> | ‘{‘ <stmt> {<stmt>} ‘}’

10. Write an EBNF rule that describes the for statement of Java or C++.
Write the recursive-descent subprogram in Java or C++ for this rule.
Assume the following non-terminals are given: <type>, <id>, <literal>, <assign>, <expr>, and <stmt_list>.
<for> -> for ‘(‘ [[<type>] <id> = <expr> {, [<type>] <id> = <expr>}] ; [<expr>] ; [<expr> {, <expr>}] ‘)’ ‘{‘ <stmt_list> ‘}’

Saturday, October 18, 2014

Assignment #3

Source:
Concepts of Programming Languages, Robert W. Sebesta.
Chapter 3: Describing Syntax and Semantics, page 162-164

By:
Name : Helena Natanael
NIM  : 1801380333



Review Question:

6. Define a left-recursive grammar rule.
When a grammar rule has its left hand side (LHS) also appearing at the beginning of its right hand side (RHS), the rule is said to be left recursive. This left recursion specifies left associativity. 

7. What three extensions are common to most EBNFs?
Extended Backus-Naur Forms has three common extensions:

1. The first extension denotes an optional part of an right hand side (RHS), which is delimited by brackets. 2. The second extension is the use of braces in an RHS to indicate that the enclosed part can be repeated indefinitely or left out altogether. 
3. The third common extension deals with multiple-choice options. When a single element must be chosen from a group, the options are placed in parentheses and separated by the OR operator, |.

8. Distinguish between static and dynamic semantics.
The static semantics of a language is only indirectly related to the meaning of programs during execution; rather, it has to do with the legal forms of programs (syntax rather than semantics).

Dynamic semantics is a perspective on natural language semantics that emphasises the growth of information in time. It is an approach to meaning representation where pieces of text or discourse are viewed as instructions to update an existing context with new information, with an updated context as result.


9. What purpose do predicates serve in an attribute grammar?
An attribute grammar consists of a grammar, a set of attributes, a set of attribute computation functions, and a set of predicates, which together describe static semantics rules. So predicates is a part of attribute grammar which is without the predicates, there would be no attribute grammar.

10. What is the difference between a synthesized and an inherited attribute
The difference between Synthesized and Inherited attribute is :
Synthesized attributes are used to pass semantic information up a parse tree, in the other hand inherited attributes pass semantic information down and across a tree.


Problem Set:

6. Using the grammar in Example 3.2, show a parse tree and a leftmost derivation for each of the following statements:

Grammar in Example 3.2:
<assign> → <id> = <expr>
<id>       → A | B | C
<expr>   → <id> + <expr>
                   | <id> * <expr>
                   | ( <expr>


a. A = A * (B + (C * A))
Parse Tree:



Leftmost Derivation:
<assign> → <id> = <expr>
               → A = <expr>              
               → A = <id> * <expr> 
               → A = A * <expr> 
               → A = A * ( <expr> )
               → A = A * ( <id> + <expr> )
               → A = A * ( B + <expr>)  
               → A = A * ( B + (<expr>) )
               → A = A * ( B + (<id> * <expr>) )

               → A = A * ( B + ( C * <expr>) )              
               → A = A * ( B + ( C * <id>) )     
               → A = A * ( B + (C * A))



b. B = C * (A * C + B)
Parse Tree:


Leftmost Derivation:
<assign> → <id> = <expr>
               → B = <expr>              
               → B = <id> * <expr> 
               → B = C * <expr> 
               → B = C * ( <expr> )
               → B = C * ( <id> * <expr> )
               → B = C * ( A * <expr>) 
               → B = C * ( A * <id> + <expr> )

               → B = C * ( A *  C + <expr> )              
               → B = C * ( A *  C + <id> )     
               → B = C * ( A * C + B )


c. A = A * (B + (C))
Parse Tree:


Leftmost Derivation:
<assign> → <id> = <expr>
               → A = <expr>              
               → A = <id> * <expr> 
               → A = A * <expr> 
               → A = A * ( <expr> )
               → A = A * ( <id> + <expr> )
               → A = A * ( B + <expr>)  
               → A = A * ( B + (<expr>) )
               → A = A * ( B + (<id>) )

               → A = A * ( B + ( C ) )                


7. Using the grammar in Example 3.4, show a parse tree and a leftmost derivation for each of the following statements:

Grammar in Example 3.4:
<assign> → <id> = <expr>
<id>       → A | B | C
<expr>   → <expr> + <term>
                    | <term>

<term>   → <term> * <factor>
                    | <factor>
<factor> → ( <expr> )
                    | <id>


 a. A = ( A + B ) * C
Parse Tree:


Leftmost Derivation:
<assign> → <id> = <expr>
               → A = <expr>
               → A = <term>
               → A = <term> * <term>  
               → A = <factor> * <term>
               → A = (<expr>) * <term> 
               → A = (<expr> + <term>) * <term> 
               → A = (<term> + <term>) * <term>   
               → A = (<factor> + <term>) * <term>    
               → A = (<id> + <term>) * <term>    
               → A = ( A + <term>) * <term>   
               → A = ( A + <factor>) * <term>     
               → A = ( A + <id>) * <term>  
               → A = ( A + B ) * <term>    
               → A = ( A + B ) * <factor> 
               → A = ( A + B ) * <id> 
               → A = ( A + B ) * C


b. A = B + C + A
Parse Tree:


Leftmost Derivation:
<assign> → <id> = <expr>
               → A = <expr>
               → A = <expr> + <term>
               → A = <term> + <term>
               → A = <factor> + <term>
               → A = <id> + <term>
               → A = B + <term>
               → A = B + <term> + <factor>
               → A = B + <factor> + <factor>
               → A = B + <id> + <factor>
               → A = B + C + <factor>             
               → A = B + C + <id>
               → A = B + C + A


c. A = A * (B + C)
Parse Tree:


Leftmost Derivation:
<assign> → <id> = <expr>
               → A = <expr>
               → A = <term> 
               → A = <factor> * <term> 
               → A = <factor> * <factor>              
               → A = <id> * <factor> 
               → A = A * <factor> 
               → A = A * ( <expr> )
                → A = A * ( <expr> + <term> )
               → A = A * ( <term> + <term> )  
               → A = A * (  <factor> + <term> )
               → A = A * ( <id> + <term> ) 
               → A = A * ( B + <term> )
               → A = A * ( B + <factor> )              
               → A = A * ( B + <id> )     
               → A = A * ( B + C )

d. A = B * (C * (A + B))
Parse Tree:



Leftmost Derivation:
<assign> → <id> = <expr>             
               → A = <expr>
               → A = <term> 
               → A = <term> * <factor> 
               → A = <factor> * <factor> 
               → A = <id> * <factor> 
               → A = B * <factor>
               → A = B * ( <expr> )
               → A = B * ( <term>) 
               → A = B * ( <term> *  <factor>) 
               → A = B * ( <factor> *  <factor>) 
               → A = B * ( <id> *  <factor>) 
               → A = B * ( C *  <factor>) 
               → A = B * ( C * ( <expr> ) ) 
               → A = B * ( C * ( <expr> + <term> ) ) 
               → A = B * ( C * ( <term> + <term> ) ) 
               → A = B * ( C * ( <factor> + <term> ) ) 
               → A = B * ( C * ( <id> + <term> ) ) 
               → A = B * ( C * (A + <term> ) )
               → A = B * ( C * (A + <factor> ) )               
               → A = B * ( C * (A + <id> ) ) 
               → A = B * ( C * (A + B ) )

8. Prove that the following grammar is ambiguous:
<S> → <A>
<A> → <A> + <A> | <id>
<id> → a | b | c

The grammar is ambiguous because there's 2 different parse trees can be made from grammar above.



9. Modify the grammar of Example 3.4 to add a unary minus operator that
has higher precedence than either + or *.

<assign> → <id> = <expr>
<id>        → A | B | C
<expr>    → <expr> + <term>   
                     | <term>
                     | - <factor>
<term>    → <term>*<factor>
                     | <factor>
<factor>  → (<expr>)
                     | <id>

10. Describe, in English, the language defined by the following grammar:
<S> → <A> <B> <C>
<A> → a <A> | a
<B> → b <B> | b
<C> → c <C> | c

It means all sentences consisting of one or more a, then a is followed by one or more b and then also followed by one or more c.